As áreas verdes de Juiz de Fora e as reservas naturais da região - Colchete Filho, Antonio; Fonseca, Fábio; Resgala, Gustavo; Muniz, Elaine; Meurer, Clara; Pereira, Amanda; Tonelli, Fernanda; Antunes, Bruno; Souza, Felipe; Creston, Helena (Principia: Caminhos da Iniciação Científica, 2018)
-